Pola Kemitraan Dalam Pengelolaan Pariwisata Di Kepulauan Karimunjawa Kabupaten Jepara - Nugroho, Sonny Setyo; Harsasto, Priyatno; Astuti, Puji (Journal of Politic and Government Studies, 2015)
ABSTRACT The Pattern Of Partnership In Tourism Development In Karimunjawa Archipelago Jepara RegencyKarimunjawa Subdistrict, Jepara regency has a key region in the tourism sector (eco) tourism-based nature is a Marine National Park Publications (TNKJ). Currently TNKJ has developed into a tourist area that became famous in the national and international arena. To realize the tourism area TNKJ more advanced and interesting course Jepara regency government should involve the cooperation of various parties. Based on these ideas, the authors conducted research on partnership in attraction Karimunjawa.This study aims to look at the fabric of partnerships between government, private and community in the management and development of the area TNKJ Tourism. In this study, researchers used a qualitative research method deskripstif by collecting data through observation, interviews and documentation. This research was conducted in the Department of Tourism and Culture of Jepara and the National Park Karimunjawa. Interviews were conducted with actors involved in the network of partnerships and competent in their respective fields.The theory explains the partnership activities performed by the actors involved. Partnership that exists in the management of tourist attraction TNKJ a collaborative partnership / multi namely the implementation of an activity or handling a problem in order to help improve the effectiveness of regional management and synergistic TNKJ jointly by the parties on the basis of understanding and mutual agreement in accordance with the legislation applies. To maximize tourism management TNKJ, then the manager in charge to coordinate cooperation and synergy, in addition to minimizing conflicts of interest that may be the case then you should lasting partnerships built on the principles of mutual respect, mutual respect, mutual trust and mutual benefits.